Turn‐On Circularly Polarized Luminescence in Metal–Organic Frameworks. Issue 23 (25th January 2021) - Wang, Xue‐Zhi; Sun, Meng‐Ying; Huang, Zhijin; Xie, Mo; Huang, Ruishan; Lu, Huihui; Zhao, Zujin; Zhou, Xiao‐Ping; Li, Dan
Abstract: The fabrication of circularly polarized luminescence (CPL) active materials by self‐assembly is still in its challenge. In this work, a family of homochiral metal–organic frameworks (MOFs) and metal–organic cages (MOCs) are constructed by solvothermal subcomponent self‐assembly. These MOFs feature an eta topology with trifold helical chains, while the MOCs adopt a cubic cage structure. The chiral ligands show two distinct types of conformations: "opened" and "closed" in MOFs and MOCs, respectively. Although homochiral MOFs and MOCs show similar spectra of circular dichroism and photoluminescence with similar quantum yields and lifetimes, the MOFs yield clear CPL signals and the CPL of MOCs are silent. The turn‐on CPL in MOFs achieved by tuning the conformation of ligands and controlling self‐assembly provides a new approach for development of CPL‐active MOF materials. Abstract : A family of homochiral metal–organic frameworks (MOFs) and metal–organic cages (MOCs) are constructed by similar ligands and ZnBr2 . The homochiral MOFs and MOCs show similar spectra of circular dichroism and photoluminescence. However, the MOFs yield clear circularly polarized luminescence (CPL) signals and the CPL of MOCs are silent, providing a new approach for development of CPL‐active MOF materials.